Reading to Young Children: Higher Home Frequency Associated with Higher Educational Achievement in PIRLS and PISA - Luisa Araújo; Patrícia Costa (Education Sciences, 2023)
The benefits of reading aloud to young children for their reading development are well documented, and international large-scale assessments (ILSAs) offer an opportunity to explore its unique contribution to literacy achievement at both the primary and secondary levels. Using Portuguese data from ILSAs, this study shows the relationship between reading to young children in the home context and their later reading performance. Specifically, we use the Program for International Reading Literacy Study (PIRLS) 2011, which tests fourth-grade students, and the Program for International Student Assessment (PISA) 2018, which is used for the assessment of 15-year-olds. Data sources from these surveys include the mean reading performance of similar cohorts of students and home/parental questionnaires that include questions about the frequency of home book-reading, as well as other background variables. Linear regression analyses show a positive and significant relationship, both at the fourth-grade level and in secondary school, between students’ performance and having been read to at home during early childhood. These findings indicate that the advantages associated with book reading in the early years are maintained throughout students’ schooling. In addition, the analysis shows that, in both surveys, girls score higher than boys in reading, and that there is a positive association between parental education and reading achievement. Implications about how children’s early literacy development sets the foundation for future educational achievement are discussed, namely in the context of country-specific reading initiatives and reading practices.